Pengenalan Google Schoolar dan Science and Technology Index (SINTA) Kepada Guru di MAN 3 Kulonprogo Yogyakarta - Benny Kurnianto; Alwazir Abdusshomad; Nawang Kalbuana; Zulina Kurniawati; Taufik Rohman; Wildan Hidayat (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Based on Minister of State Administrative and Bureaucratic Reform Regulation No. 16 of 2009 concerning Functional Positions of Teachers and Their Credit Scores, the publication of scientific papers is one of the requirements for promotion for a teacher. Based on observations, teachers at MAN 3 Kulonprogo still need training on how to publish scientific papers. The publication of scientific work can be recognized as a requirement if the publication is recorded on a scientific work database such as the Google Schoolar and Science and Technology Index (SINTA). For this reason, teachers need to receive training to increase their knowledge of the benefits of indexing scientific journals. The strategy applied in this community service activity is the use of online lectures, practice questions, and questions and answers which are carried out through the Zoom Meeting program. After receiving the training, the knowledge value of the teachers participating in the training increased by 2.221 compared to before they were given material on Google Schoolar and the SINTA Index. In addition, the results of the Paired Sample T-Test showed a sig value of 0.048 and less than 0.05 (alpha 5%) indicating that this PKM activity had an impact on the teachers of MAN 3 Kulonprogo Yogyakarta, especially in terms of increasing their capacity to operate the Google Schoolar application and Science and Technology Index (SINTA) as a scientific publication indexation database.